Cytotoxic Activity of Secondary Metabolites from the Bark of Dipterocarpus Confertus Sloot (JOURNAL OF ADVANCES IN CHEMISTRY, 2013)
Four compounds, namely Î²-sitosterol (1), betulinic acid (2), cinnamic acid (3), and Î±-viniferin (4) have been successfully isolated from the bark methanol extract of Dipterocarpus confertus Sloot. The structures of the isolated compounds have been established on the basis spectroscopic data evidence, and comparison with the published data. In the cytotoxicity study, cinnamic acid (3) and betulinic acid (2) have been found to be very strong active against murine leukemia P388 and vero cells lines with the IC50 values of 2.25 and 5.10 Âµg/mL, respectively, while the other compounds were not active.